2002
DOI: 10.1016/s1090-7807(02)00033-2
|View full text |Cite
|
Sign up to set email alerts
|

Application of REDOR subtraction for filtered MAS observation of labeled backbone carbons of membrane-bound fusion peptides

Abstract: Clean MAS observation of 13 C-labeled carbons in membrane-bound HIV-1 and influenza fusion peptides was made by using a rotational-echo double-resonance spectroscopy (REDOR) filter of directly bonded 13 C-15 N pairs. The clean filtering achieved with the REDOR approach is superior to filtering done with sample difference spectroscopy. In one labeling approach, the peptide had labels at a single 13 C carbonyl and its directly bonded 15 N. The resulting chemical shift distribution of the filtered signal is used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
54
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 70 publications
5
54
0
Order By: Relevance
“…For the HFP3-8 FLG and HFP2-14 AAG samples associated with PC:PG, there were shoulders at ~178 and 179 ppm, respectively, which correlated with helical conformation of Ala, Leu, and Phe residues. These results were consistent with previous studies of the conformation of membrane-associated HFP with peptide:lipid ~ 0.04 and with previous observations of greater preference for β strand conformation in cholesterol-containing membranes (27,28,35,55,56,59,70). The data demonstrated that samples containing HFP2-14 AAG have qualitatively larger (ΔS/ S 0 ) exp than do samples containing HFP labeled at other residues.…”
supporting
confidence: 92%
“…For the HFP3-8 FLG and HFP2-14 AAG samples associated with PC:PG, there were shoulders at ~178 and 179 ppm, respectively, which correlated with helical conformation of Ala, Leu, and Phe residues. These results were consistent with previous studies of the conformation of membrane-associated HFP with peptide:lipid ~ 0.04 and with previous observations of greater preference for β strand conformation in cholesterol-containing membranes (27,28,35,55,56,59,70). The data demonstrated that samples containing HFP2-14 AAG have qualitatively larger (ΔS/ S 0 ) exp than do samples containing HFP labeled at other residues.…”
supporting
confidence: 92%
“…REDOR-filtered experiments as described in the literature (47) were utilized to suppress the 13 C background signal from lipids of MLVs. A 5mm triple-resonance Varian/Chemagnetics MAS probe was used and the sample was spun at a speed of 8 kHz spinning speed at −20°C.…”
Section: Magic Angle Spinning Solid-state Nmr Experimentsmentioning
confidence: 99%
“…For the S 1 acquisition, a 15 N 180°pulse at the middle and end of each rotor period in the dephasing time was applied. Other details of the REDOR filtering experiment can be found elsewhere (28). Spectra of DMPC MLVs containing 3 mol % pardaxin suggest that the 13 C-labeled site ( 13 CЈ-Leu) has an isotropic chemical shift value (referenced relative to tetramethylsilane) in the range characteristic of residues in an ␣-helical conformation (10,29,30).…”
Section: Structure Of Pardaxin 45816mentioning
confidence: 99%